2009
DOI: 10.1016/j.nano.2008.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial permeability is controlled by spatially defined cytoskeletal mechanics: Atomic force microscopy force mapping of pulmonary endothelial monolayer

Abstract: Actomyosin contraction directly regulates endothelial cell (EC) permeability, but intracellular redistribution of cytoskeletal tension associated with EC permeability is poorly understood. We used atomic force microscopy (AFM), EC permeability assays and fluorescence microscopy to link barrier regulation, cell remodeling and cytoskeletal mechanical properties in EC treated with barrierprotective as well as barrier-disruptive agonists. Thrombin, VEGF and H 2 O 2 increased EC permeability, disrupted cell junctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
78
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 56 publications
12
78
0
Order By: Relevance
“…6Biv,v,C). These results are highly consistent with a previous study that coordinately assessed barrier function, actin remodeling and local cell stiffness (but not diapedesis) in endothelium in response to related barrier-modifying stimuli (Birukova et al, 2009). These experiments suggest that barrier-altering regimes promote changes in junctional stiffness that ILPs would identify.…”
Section: Ilps Might Function In Local Sampling Of Endothelial Stiffnesssupporting
confidence: 91%
“…6Biv,v,C). These results are highly consistent with a previous study that coordinately assessed barrier function, actin remodeling and local cell stiffness (but not diapedesis) in endothelium in response to related barrier-modifying stimuli (Birukova et al, 2009). These experiments suggest that barrier-altering regimes promote changes in junctional stiffness that ILPs would identify.…”
Section: Ilps Might Function In Local Sampling Of Endothelial Stiffnesssupporting
confidence: 91%
“…Atomic force microscopy (AFM) studies revealed that a single cell in a monolayer of HUVECs or bovine aortic ECs, either inflamed or non-inflamed, is stiffer at the cell periphery compared to the cell center and the nucleus (Sato et al, 2000;Schaefer et al, 2014;Stroka and Aranda-Espinoza, 2011a). However, it has also been shown that non-inflamed HUVECs have a softer cell periphery compared to their nucleus and that non-inflamed ECs from human pulmonary aortas show no stiffness gradient (Birukova et al, 2009;Mathur et al, 2001). These discrepancies might be due to the differences in cytokine stimulation, the cell type used, and experimental conditions, such as the size and geometry of the AFM probe.…”
Section: Mechanotransduction In Ecs Substrate Stiffness Controls Endomentioning
confidence: 99%
“…Birukova et al analysed nonTNFa-treated human pulmonary arterial endothelial cells using a 30-nm tip as compared to a 10-mm bead, which is similar to the size of a neutrophil, as used in our assays (Birukova et al, 2009). They detected, in contrast, hardly any differences in elastic module between the periphery and the centre of the resting cells.…”
Section: Actin-binding Proteins Differentially Regulate Endothelial Cmentioning
confidence: 99%